Can Heteroarenes/Arenes Be Hydrogenated Over Catalytic Pd/C Under Ambient Conditions?. Issue 34 (20th July 2020) - Tanaka, Nao; Usuki, Toyonobu
Abstract : Hydrogenation of over a dozen aromatic compounds, including both heteroarenes and arenes, over palladium on carbon (Pd/C, 1–100 mol%) with H2 ‐balloon pressure at room temperature is reported. Analyses using pyridine as a model substrate revealed that acetic acid was the best solvent, as using only 1 mol% Pd/C provided piperidine quantitatively. Substrate scope analysis and density functional theory calculations indicated that reaction rates are highly dependent on frontier molecular orbital characteristics and the steric bulkiness of substituents. Moreover, the established method was used for the concise synthesis of the anti‐Alzheimer drug donepezil (Aricept®). Abstract : Pd/C‐mediated dearomatic hydrogenation under ambient conditions such as balloon pressure and room temperature can be a powerful tool for constructing alicyclic skeletons. Density functional theory calculations have been performed to confirm the mechanistic aspects and the utility of the established methodology has been demonstrated by donepezil synthesis.